2009
DOI: 10.1128/jcm.01437-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatitis C Virus Core Antigen Assays in Detecting Recombinant Viral Antigens of Various Genotypes

Abstract: A single substitution within the hepatitis C virus core antigen sequence, A48T, which is observed in ϳ30% of individuals infected with genotype 2a virus, reduces the sensitivity of a commonly used chemiluminescence enzyme immunoassay. Quantitation of the antigen is improved by using a distinct anticore antibody with a different epitope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…S4 in the supplemental material). These results are consistent with our previous study, which suggested that core Ag levels of HCV strain JFH-1 were underestimated by the Lumipulse-Ag kit in comparison to the ELISA-Ag assay (28). Strain JFH-1 harbors an Ala-to-Thr substitution at aa 48; conversion of Thr to Ala at this position in JFH-1 was sufficient to overcome this underestimation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…S4 in the supplemental material). These results are consistent with our previous study, which suggested that core Ag levels of HCV strain JFH-1 were underestimated by the Lumipulse-Ag kit in comparison to the ELISA-Ag assay (28). Strain JFH-1 harbors an Ala-to-Thr substitution at aa 48; conversion of Thr to Ala at this position in JFH-1 was sufficient to overcome this underestimation.…”
Section: Discussionsupporting
confidence: 82%
“…Although core Ag levels are thought to be related closely to HCV RNA titers, the correlation and linearity of core Ag levels have not yet been fully evaluated. In addition, these quantitative parameters are known to be affected by nucleotide and amino acid sequences at the target regions of the assays (5,6,28,34), and this sequence variation depends on genotypes or predominant strains in specific geographical regions.…”
mentioning
confidence: 99%
“…9B). This discrepancy may be due to the lower detection efficiency of the JFH-1 core protein in the immunoassay, as reported previously (31). Infectivity in the culture medium was also determined.…”
Section: Resultsmentioning
confidence: 92%
“…Synthesized HCV RNA (10 g) was transfected into Huh-7.5.1 or Huh7-25 cells. HCV core protein levels in the culture medium were measured by immunoassay (31). HCV RNA levels in the culture medium were quantified as described above.…”
Section: Figmentioning
confidence: 99%
“…The resultant fragments were cloned into pCAGGS. Plasmids for expression of FLAG-tagged core derives from genotype 1a, 2a and 3a were described previously (Saeed et al, 2009). Pol I-driven HCV genome plasmid (genotype 2a) pHHJFH1am was described previously (Suzuki et al, 2012).…”
Section: Methodsmentioning
confidence: 99%